THE EFFECT OF FOREIGN DIRECT INVESTMENT ON LABOUR PRODUCTIVITY: EVIDENCE FROM FIVE INVESTOR COUNTRIES IN THE MALAYSIAN MANUFACTURING INDUSTRIES (Malaysian Management Journal, 2022)
This study has utilised the Seemingly Unrelated Regression (SUR) estimator method to explore the spillover effects of “technology” and “knowledge” from foreign direct investment (FDI) on Malaysian labour productivity. The study focus was on Malaysian medium-low technology and low-technology industries from 2000 to 2018. The findings showed that the presence of FDI spillovers as diffusion channels that increased labour productivity were greater through “technology effects” compared to “learning effects” for both types of industries. A cross-comparison of the results on technological spillovers between investor countries revealed that Singaporean and Japanese multinational corporations (MNCs) contributed the most significant technological effects in increasing Malaysian labour productivity, with the effects being most noticeable was in low-technology industries. These findings seem to suggest that the spillover effects of FDI are still concentrated in sectors with low-capacity technologies that commensurate with the required level of workforce capability. The negative relationship between “knowledge” spillovers and productivity found in this study seems to illustrate that the absorptive capacity of local workers to absorb high-skill-based technology from MNCs is still at a low level in both types of industries. This study has recommended that strategies and mechanisms should be devised accordingly to assist MNCs in their effort to improve knowledge and technology transfers, while simultaneously acknowledging the constraints of human factors, absorptive capacity, competition for resources or ethical dilemmas and cultural barriers.